2022
DOI: 10.1002/joc.7617
|View full text |Cite
|
Sign up to set email alerts
|

Two spatial types of North China heatwaves and their possible links to Barents‐Kara Sea ice changes

Abstract: Heatwaves of different spatial types can cause various impacts. Based on the spatial heatwave intensity, 47 North China heatwaves from 1961 to 2019 could be classified into two categories: the S‐type with a centre in the south and the N‐type in the north. There were more N‐type events (36) than the S‐type (11). Observational analysis indicated that under atmospheric circulations favourable to North China heatwaves (e.g. the enhanced continental high), there is a linkage between the sea ice concentration (SIC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The area of 35°–45°N, 110°–120°E within China is defined as North China (Figure S1), consistent with previous studies (Zhang et al, 2020b, 2022). This region includes Beijing, Tianjin, Hebei, Shanxi, as well as parts of Inner Mongolia and Shandong.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The area of 35°–45°N, 110°–120°E within China is defined as North China (Figure S1), consistent with previous studies (Zhang et al, 2020b, 2022). This region includes Beijing, Tianjin, Hebei, Shanxi, as well as parts of Inner Mongolia and Shandong.…”
Section: Methodssupporting
confidence: 87%
“…Super heatwaves in 2021 killed more than 500 people and caused 180 wildfires across North America (Schiermeier, 2021). Heatwaves in China also resulted in serious negative impacts (Cai et al, 2021; Zhang et al, 2022). The 2013 heatwave led to about 160 deaths in Shanghai, and many provinces experienced unprecedented heatwaves costing about $10 billion in damages (Sun, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as global warming intensifies, Arctic Sea ice will decrease significantly, and its potential impact on climate changes in the middle and high latitudes of the Northern Hemisphere will increase during the summer months. Several studies have found that warm‐season Arctic Sea ice may be linked to the teleconnection wave trains over Eurasia through meridional anomalous circulation patterns, affecting extreme climate events at middle and high latitudes (Zhang et al, 2022). Some studies also suggest that there exist SST anomalies at high latitudes responding to overlying atmospheric anomalies, which means that the atmosphere could force SST (Chen et al, 2016; Wu & Chen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the daily maximum temperature (Tmax), we used the 95th percentile of Tmax of the study period as the threshold ( Tx95 ) to select EHT days for each grid in CA (Meehl & Tebaldi, 2004; Zhang et al, 2022). An EHT event is recognized to occur when Tmax exceeds Tx95 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation